The Concept of Education Perspective Ibn Qayyim al-Jawziyya - Bermi, Wibawati; Musfiratul, Indah; Mu'amar Rifqi, Akhlish (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2023)
This research aims to explore the concept of education according to Ibn Qayyim al-Jawziyya, a prominent Islamic scholar and thinker. Its primary objective is to comprehend his views on education as reflected in his works and to analyze the holistic approach he advocated for shaping individuals in accordance with Islamic principles. The research employs a method of classical text analysis and literature review. Through the analysis of Ibn Qayyim's works and previous research, the researcher delves into his perspectives on education and the methods he recommended for character formation and intellectual development of individuals. The findings of the research indicate that Ibn Qayyim advocates for holistic education, encompassing character formation, spiritual growth, and the integration of knowledge and morality. He emphasizes the importance of education centered on Islamic values to create individuals of quality who can contribute positively to society. Based on the research findings, it is recommended to integrate Ibn Qayyim's educational concepts into formal educational curricula, provide training to educators in implementing the methods of education recommended by him, and further research to delve into the relevance of these concepts in the context of modern education.